Characterization and use of a vegetable waste vermicompost as an alternative component in substrates for horticultural seedbeds - Melgar-Ramirez, R.; Pascual-Alex, M. I. (Spanish Journal of Agricultural Research, 2010)
This experiment was designed to characterize the physical and chemical properties of six crop’s media obtained by mixing different percentages (v/v) of peat, perlite, coconut coir dust, and vermicompost (end-product of the breakdown of organic matter of crop residues mixed with re-used coconut coir dust by Eisenia fetida) and to evaluate the tomato (Solanum lycopersicum cv. cumquat) seedling growth in this media. The treatments were: T1 (75% peat and 25% perlite), T2 (25% peat, 25% coconut coir dust, 25% vermicompost and 25% perlite), T3 (50% peat, 25% vermicompost and 25% perlite), T4 (25% peat, 50% vermicompost and 25% perlite), T5 (50% coconut coir dust, 25% vermicompost and 25% perlite), T6 (25% coconut coir dust, 50% vermicompost and 25% perlite). The electrical conductivity, pH, bulk density and water-soluble elements, contained in the substrate, increased with increasing amounts of vermicompost in the substrate, whereas the total porosity, easily available water and total water holding capacity decreased significantly with increasing amounts of vermicompost. Stem length and leaf area of tomato seedlings were higher in the substrate without vermicompost (T1) but no significant differences were found between substrates with vermicompost. No significant difference was found in the production of roots dry weight in all treatments; this is a very important result, because good quality of root system is the main goal in seedbeds. There are not clear relationships between the increase of vermicompost in mixtures and nutrient contents in stems and leaves.